Ascertaining the link between dengue and climatic conditions - Arcenas, Agustin (Philippine Review of Economics, 2016)
I examine climate-change related factors affecting the incidence of dengue in the Philippines. Dengue is estimated to cost hundreds of millions of dollars in the Philippines and worldwide in terms of treatment, surveillance and control, lost income, and other indirect costs per year. The disease is a burden especially for the poor, who are less able to access funds for treatment and are more heavily affected by the loss in income due to illness.